PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR (STUDI PADA PENGGUNA HONDA VARIO 125CC DI PONTIANAK) - B31112018, HURYANSYAH (Jurnal Manajemen Update, 2016)
Sales of Honda Vario 125cc in 2013 and 2015 experienced a slight increase and Honda Vario 125cc survive rated second from 2013 until 2015, Honda Vario motorcycle is the first automatic manufactured by Honda, the type of category Honda Vario taken in this research that Honda Vario 125cc. This study aims to determine: (1) to test and analyze the quality of products on purchase decisions motorcycles 125cc Honda Vario in Pontianak. (2) To examine and analyze the effect of price on purchase decisions Motorcycles 125cc Honda Vario in Pontianak. (3) To examine and analyze the effect of brand image on purchase decisions Motorcycles 125cc Honda Vario in Pontianak. This research is a causal research design, while the population in this study is the buyer's decision and the 125cc Honda Vario in Pontianak. Technique sampling Theused in this research is using purposive sampling, as for the sample of 100 respondents of this study, which is the buyer's decision and the 125cc Honda Vario in Pontianak. The analytical tool used multiple linear regression by first tested the validity, reliability and classic assumption. The results showed that all three variables such as product quality, price, and brand image positive and significant impact on purchasing decisions Honda Vario 125cc in Pontianak.   Keywords: Product Quality, Price, Brand image, Purchase Decision.